Raised without antibiotics: impact on animal welfare and implications for food policy. Issue 4 (10th August 2018) - Karavolias, Joanna; Salois, Matthew Jude; Baker, Kristi T; Watkins, Kevin
Abstract: This study assesses the impact of broilers raised without antibiotics and the information gap that exists between consumer perception and production methods. Specifically looking at risk of eye burns, footpad lesions, and airsacculitis, key indicators of animal welfare, bird-level data are collected on the occurrence and severity of each disease state by the type of antibiotic program: no antibiotics ever, nonmedically important antibiotics, or medically important antibiotics. Odds ratios and marginal effects are calculated to understand how the occurrence and severity change with access to medicine. Broilers never given antibiotics had a higher likelihood of disease states investigated, and with greater severity. In some cases, access to nonmedically important ionophores mitigated the risk of occurrence and severity of the conditions. The finding indicates that the growing trend of raising broilers without antibiotics may negatively affect animal welfare. This stands in contrast to existing consumer research showing that consumers purchase poultry raised without antibiotics because they believe that it promotes healthier animals. Therefore, a significant consumer information gap exists which needs to be addressed. JEL Codes: Q130, Q160, Q180